The Effect of Extraction Duration and Concentration of Ethanol Solvent to the Extraction of Cocoa Beans (Theobroma cacao L) Antioxidant - Diantika, Fitrah; Sutan, Sandra Malin; Yulianingsih, Rini (Jurnal Teknologi Pertanian, 2014)
Antioxidant is a substance that can inhibit or slow down the oxidation process and is able to counteract the negative effects of oxidants in the body that are beneficial to health. Antioxidants can be found in vegetables, fruits, tea and chocolate. Antioxidants can be obtained by extraction. The purpose of this study was to assess the effect of long extraction and ethanol concentration on the extraction yield results, antioxidant activity and calculate the mass balance process. The materials used are cocoa (Theobroma cacao L). Research compiled using Randomized Block Design (RBD) with two factors: the long process of extraction by maceration namely (8,12,16,20 and 24 hours) and ethanol concentration of 70% and 80%. The results showed that the best treatment was obtained from the 20-hour long extraction and ethanol concentration of 80% for the antioxidant activity IC50 of 82 ppm and a yield of 8.63%.Keywords: Antioxidants, Extraction, Ethanol, Cocoa, Old Extraction.